Giant pandas’ staple food bamboo phyllosphere fungal community and its influencing factors - Kang, Liwen; Luo, Wei; Dai, Qinglong; Zhou, Hong; Wei, Wei; Tang, Junfeng; Han, Han; Yuan, Yuan; Long, Juejie; Zhang, Zejun; Hong, Mingsheng (Frontiers in Microbiology, 2022)
Giant pandas have developed a series of foraging strategies to adapt to their special bamboo diets. Although bamboo is an important food resource for giant pandas in Liziping National Nature Reserve (Liziping NR), China, there are relatively few studies on their phyllosphere fungal community and its influencing factors. Herein, we used ITS1 amplification and metagenomic sequencing to analyse the phyllosphere fungi diversity and functions (KEGG, CAZyme and antibiotic resistance gene) and explore the influencing factors for the three giant pandas foraging bamboo species (Arundinaria spanostachya, AS; Yushania lineolate, YL; Fargesia ferax, FF) over different seasons (spring vs. autumn) in Liziping NR, China. We found that Ascomycota and Basidiomycota were the most dominant phyla in the bamboo phyllosphere. The alpha diversity (e.g. the Sobs index and Shannon index) was relatively higher in autumn samples than in spring samples, and the community structure differed significantly between the three bamboo species in spring and autumn. Some biotic and abiotic variables (e.g. the elevation and mean base diameter of bamboo) significantly influenced the abundance, diversity, and community structure of the bamboo phyllosphere fungal community. Moreover, the functional analysis showed the differences in the glycoside hydrolase community and antibiotic resistance gene (ARG) profile between spring and autumn samples. Co–occurrence network modelling suggested that AS phyllosphere fungal communities in autumn employed a much more complex network than that in spring, and the abundance of multidrug, tetracycline, and glycopeptide resistance genes was high and closely correlated with other ARGs. These results indicate that fungal community’s abundance, diversity, and community structure are mainly affected by the season, host species, and elevation. The season and host species are major factors affecting the biological functions (KEGG and CAZyme), ARGs, and interactions between sympatric bacterial and fungal communities in bamboo phyllosphere. This integrated study can provide a reference basis for the seasonal management of bamboo resources foraged by wild giant pandas, and predict the risk of antibiotic resistance in bamboo phyllosphere fungal flora in Liziping NR (Xiaoxiangling mountains), China.